2009
DOI: 10.1177/1744987109352929
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in an action research project: 5 years of a Dignity and Respect action group in a hospital setting

Abstract: In March 2004 we delivered a new module entitled 'Fostering Dignity and Respect in Health CareSettings. This was a collaborative venture between Anglia Ruskin University lecturers and Southend University Hospital Staff and was the first step in our Action Research project. We had expected the project to be a short term one terminating with the first 3 deliveries of the module. However the education programme led to the formation of a Dignity and Respect Action Group within the hospital that continues to this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…Crow et al . ). Additionally, the involvement of a range of stakeholders also ensures that any interventions are tailored to the actual needs of the organisation, rather than to assumptions.…”
Section: Key Issuesmentioning
confidence: 97%
See 1 more Smart Citation
“…Crow et al . ). Additionally, the involvement of a range of stakeholders also ensures that any interventions are tailored to the actual needs of the organisation, rather than to assumptions.…”
Section: Key Issuesmentioning
confidence: 97%
“…There is also the added potential benefit that impacts may be long-lasting as a consequence of shared ownership (e.g. Crow et al 2010). Additionally, the involvement of a range of stakeholders also ensures that any interventions are tailored to the actual needs of the organisation, rather than to assumptions.…”
Section: Key Issuesmentioning
confidence: 99%
“…To realize sustainability, good leadership and a management of the good care are needed, which also necessitates an engaged, knowledgeable and well‐educated staff (Crow et al . , Bookbinder et al . , Parson & Cornett , Gloppen et al .…”
Section: Introductionmentioning
confidence: 99%
“…The creation of ethically sustainable care contexts is based on economically stable evidence-based care models, a respectful and dignified care and a thinking that revolves around health. To realize sustainability, good leadership and a management of the good care are needed, which also necessitates an engaged, knowledgeable and well-educated staff (Crow et al 2010, Bookbinder et al 2011, Parson & Cornett 2011, Gloppen et al 2012. Wallinvirta (2011) views the act of management as a mission: to with responsibility and love cherish and serve life.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainability in healthcare is generated by creating and implementing evidence-based care models that are enduring, embraced by an organization’s entire staff and work as indicators of healthcare. 6,7,9 13 In line with Världsmedborgaren’s thinking, Crow et al 10 found that ethics is the foundation for sustainability in healthcare. They highlight the ethical values respect and dignity as the starting point for sustainability.…”
Section: Introductionmentioning
confidence: 90%